Spatial and temporal distribution of bat mortality on a highway in southeast Brazil - Brito de Oliveira, Marcione; Bueno, Cecília (THERYA, 2022)
Roads and highways can work as barriers to the movement of many species, thereby preventing the individuals from accessing feeding and reproduction sites and the immediate risk of colliding wild species with vehicles. Identifying the impacts of roads on wildlife can contribute to the establishment of actions that promote conservation. In Brazil, data on collisions between bats and vehicles are scarce and underestimated in the literature. We described bat roadkill from 2008 to 2019 on a stretch of the BR-040 highway, which crosses an area of Atlantic Forest. Roadkill species were identified and the sites with high collision frequencies were characterized. A total of 923 individuals of 57 species and five families of chiropterans were identified. Frugivore bats showed the largest number of affected individuals, with Artibeus lituratus, a common species in the study region, with the highest number of roadkills. The diet and foraging behaviour were the most likely factors explaining most of the bats killed on the highway. The highest roadkill rate was documented in the fall, and the critical points located nearby the APA Petrópolis and REBIO of Tinguá, environmental protection areas. We reinforce the need to mitigate these roadkills, ensuring that road systems, which constitute municipal, state and federal highways, are built to prevent major disturbance of habitat and displacement routes of these species. We believe in the need for mitigations, and considering the various species involved, we suggest speed bumps construction reducing the speed limit, installing bridges, and signaling the presence of wildlife, before the stretches identified as hotspots.